Services Trade in the Balkans - Michalopoulos, Constantine (Washington, DC: World Bank, 2013)
This study aims at providing an overview of policies affecting services trade in seven countries of the Balkan region, and stresses the growing importance of services trade. The service sectors, particularly tourism and transport, play an important role in the economies of the Balkan countries. The paper finds that, on average, the countries involved, are committed to a liberal trade regime for services, and that they have made more commitments to liberalize services in the World Trade Organization (WTO) than developing countries at comparable levels of development. For the future, the paper encourages further liberalization at the regional level, on a Most Favoured Nation (MFN) basis, as well as policy harmonization with the European Union.